CME propagation through the heliosphere: Status and future of observations and model development - Manuela Temmer; Camilla Scolini; Ian G. Richardson; Stephan G. Heinemann; Evangelos Paouris; Angelos Vourlidas; Mario M. Bisi; N. Al-Haddad; T. Amerstorfer; L. Barnard; D. Burešová; S.J. Hofmeister; et al. (Advances in Space Research, 2023)

Translating climate beliefs into action in a changing political landscape - Stephanie J. Zawadzki; Thijs Bouman; Linda Steg; Vladimir Bojarskich; Perri B. Druen (Climatic Change, 2020)
Political leaders can influence public beliefs about climate change, and climate beliefs can influence climate actions. But, much is still unknown about (1) whether changes in political landscapes influence public’s climate beliefs and (2) the psychological process through which climate beliefs influence pro-environmental sentiments and actions. Achieving a better understanding these influences are the dual purposes of this paper, we investigated during the unique setting of the 2016 US presidential elections. First, we explored to what extent the American public’s belief in the anthropogenic origins and negative impacts of climate change were influenced by the 2016 US presidential election and earliest administrative days of a climate-skeptical political leader, Donald Trump. We found Trump’s influence on public climate beliefs may have increased after his election in such a way that may have polarized public climate beliefs. Compared with pre-election levels, supporters’ climate beliefs grew weaker and, further, opponents’ climate beliefs grew stronger after his election. Second, we tested a novel conditional mediation model that proposes climate beliefs interact to exert their influence on climate actions via moral behavioral sentiments. Specifically, we found people’s origin and impact climate beliefs interact to influence climate actions by activating moral sentiments about their own environmental behavior (i.e., guilt, striving to be a better person), with the particularly weak moral sentiments reported by those with both weak belief in climate change’s anthropogenic origins and its negative impacts. Moral sentiments, in turn, predicted respondents’ willingness to save energy to reduce climate change and their support for the Paris Climate Agreement. These results suggest the election of climate-skeptical political leaders can impact the public’s climate beliefs. Moreover, climate beliefs interact to influence the moral sentiments people feel about their own behavior, and consequently, influence their climate-friendly behavioral intentions and policy preferences.

Characterization of OATP1B3 and OATP2B1 transporter expression in the islet of the adult human pancreas - Michelle Kim; Perri Deacon; Rommel G. Tirona; Richard B. Kim; Christopher L. Pin; Henriette E. Meyer zu Schwabedissen; Rennian Wang; Ute I. Schwarz (Histochemistry and Cell Biology, 2017)

Erratum to: Cortical reorganization in an astronaut’s brain after long-duration spaceflight - Athena Demertzi; Angelique Van Ombergen; Elena Tomilovskaya; Ben Jeurissen; Ekaterina Pechenkova; Carol Di Perri; Liudmila Litvinova; Enrico Amico; Alena Rumshiskaya; Ilya Rukavishnikov; Jan Sijbers; Valentin Sinitsyn; et al. (Brain Structure and Function, 2016)

Cortical reorganization in an astronaut’s brain after long-duration spaceflight - Athena Demertzi; Angelique Van Ombergen; Elena Tomilovskaya; Ben Jeurissen; Ekaterina Pechenkova; Carol Di Perri; Liudmila Litvinova; Enrico Amico; Alena Rumshiskaya; Ilya Rukavishnikov; Jan Sijbers; Valentin Sinitsyn; et al. (Brain Structure and Function, 2016)

Multivalent proteoglycan modulation of FGF mitogenic responses in perivascular cells - Sabrina Cattaruzza; Ugur Ozerdem; Martin Denzel; Barbara Ranscht; Pietro Bulian; Ugo Cavallaro; Daniela Zanocco; Alfonso Colombatti; William B. Stallcup; Roberto Perris (Angiogenesis, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

An intimate interplay between precocious, migrating pericytes and endothelial cells governs human fetal brain angiogenesis - Daniela Virgintino; Francesco Girolamo; Mariella Errede; Carmen Capobianco; David Robertson; William B. Stallcup; Roberto Perris; Luisa Roncali (Angiogenesis, 2007)